Epidemiological characteristics of patients diagnosed with dengue from 2015 to 2020 in Celaya, Guanajuato, México - Isaac Soriano Rodríguez; Luz María Cardona Torres (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Dengue is a viral disease transmitted by arthropods. It is caused by four Ribonucleic Acids (RNA) flavivirus serotypes (dengue virus [DENV] -1, -2, -3, and -4) which are transmitted by blood-feeding mosquitoes, primarily the Aedes aegypti mosquito. The infection causes flu-like symptoms and sometimes progresses to death.